Physical and durability properties of recycled polyethylene terephthalate (PET) fibre reinforced concrete - Sayi, Can Ozgun; Eren, Ozgur (Taylor & Francis Ltd, 2022)
Utilisation of recycled Polyethylene Terephthalate (PET) waste in construction materials contributes towards the environmental sustainability by reducing the accumulation of non-degradable waste into the nature. This study aims to contribute to the knowledge about the material behaviour of recycled PET fibre reinforced concrete (RPFRC). The present work investigates the influence of recycled PET fibres on the physical properties of concrete, with a focus on the durability, acoustic properties, and the mechanical response to heat exposure. Mixtures with varying fibre dimensions and fibre volumes were prepared. Fibre addition reduced the bulk density, increased the permeable void volume, and decreased the ultrasonic pulse velocity (UPV) of concrete, suggesting possible porosity formations within. Water permeability of RPFRC samples was substantially higher than the concrete without fibres and the findings were in agreement with rapid chloride permeability test results. Sound permeability was slightly reduced by fibre addition. RPFRC samples were heated at three different temperatures and tested for compressive and flexural strengths. At room temperature, fibre addition caused negligible variations in compressive strength but notable increase in flexural strength. Strength values were reduced slightly with fibre addition when samples were exposed to 100 degrees C and 200 degrees C, indicating possible response of PET fibres to high-temperature exposure.
Keywords: Recycled PET fibre; waste utilisation; durability; compressive strength; flexural strength; heat exposure